2018
DOI: 10.1186/s13071-018-2706-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in the abundance of Culicoides biting midges (Diptera: Ceratopogonidae) in nine European countries

Abstract: BackgroundBiting midges of the genus Culicoides (Diptera: Ceratopogonidae) are vectors of bluetongue virus (BTV), African horse sickness virus and Schmallenberg virus (SBV). Outbreaks of both BTV and SBV have affected large parts of Europe. The spread of these diseases depends largely on vector distribution and abundance. The aim of this analysis was to identify and quantify major spatial patterns and temporal trends in the distribution and seasonal variation of observed Culicoides abundance in nine countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 58 publications
5
54
0
1
Order By: Relevance
“…Neither of these two species were recorded in the collections from Italy. These results are in line with previous findings in Sweden, The Netherlands, and Italy that demonstrated that the two species of the Obsoletus complex are the dominant species in the Obsoletus group across Europe (Meiswinkel et al 2008;Nielsen et al 2010;Goffredo et al 2016;Cuéllar et al 2018;Magliano et al 2018). However, earlier research described the presence of the four species in each of the countries.…”
Section: Discussionsupporting
confidence: 93%
“…Neither of these two species were recorded in the collections from Italy. These results are in line with previous findings in Sweden, The Netherlands, and Italy that demonstrated that the two species of the Obsoletus complex are the dominant species in the Obsoletus group across Europe (Meiswinkel et al 2008;Nielsen et al 2010;Goffredo et al 2016;Cuéllar et al 2018;Magliano et al 2018). However, earlier research described the presence of the four species in each of the countries.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, all putative vectors of BTV and SBV in northern Europe were identified at both zoos. All species collected had been previously identified within the UK and the species composition at each zoo is typical of that found at livestock farms across northern Europe [31,34,43]. The findings are also consistent with the species composition found at Chester Zoo previously [21], where 25 species of Culicoides were identified.…”
Section: Discussionsupporting
confidence: 83%
“…The expansion of BTV from the Mediterranean basin to central Europe up to Scandinavia [9][10][11] prompted studies on Culicoides taxonomy [12][13][14], ecology [15][16][17] and vector competence [18][19][20]. In contrast, only few studies focused on the Culicoides fauna in southeastern Europe.…”
mentioning
confidence: 99%